Intelligibility research in Brazil: empirical findings and methodological issues - Gonçalves, Alison Roberto; Silveira, Rosane (Revista Horizontes de Linguistica Aplicada, 2015)
Abstract The current paper addresses intelligibility, a dimension used to assess second language speech, which has also been proposed as one of the goals in pronunciation instruction. Studies carried out on this construct in Brazil are revisited (BECKER, 2013; CRUZ, 2005; 2006; 2008, 2012a, 2012b; CRUZ; PEREIRA, 2006; GONÇALVES, 2014; REIS; CRUZ, 2010; RIELLA, 2013; SCHADECH, 2013), and their main findings are discussed taking into account Jenkins’ (2002) Lingua Franca core. Furthermore, methodological issues are discussed, pointing out the different foci of the studies conducted in Brazil, the variables examined by the Brazilian studies at present, and the myriad of variables contemplated by international studies that still need investigation in the Brazilian context. Some of these variables are related to the speaker/listener or are of linguistic nature (e.g., L2 proficiency, accent familiarity, lexical frequency), all of which could help us to understand the intelligibility construct. Finally, the paper brings concluding remarks about the investigation of intelligibility and possible implications for the classroom and the research realms. Keywords: Intelligibility; Brazilian English; Research method; Pronunciation assessment. A pesquisa em inteligibilidade no Brasil: resultados empíricos e questões metodológicas Resumo Este artigo tem como foco a inteligibilidade, uma dimensão utilizada para avaliar a fala na segunda língua, que também foi proposta como uma das metas para o ensino de pronúncia na sala de aula. Estudos realizados no Brasil são revisitados BECKER, 2013; CRUZ, 2005; 2006; 2008, 2012a, 2012b; CRUZ; PEREIRA, 2006; GONÇALVES, 2014; REIS; CRUZ, 2010; RIELLA, 2013; SCHADECH, 2013) e os principais achados desses estudos são discutidos, levando-se em consideração a proposta de Jenkins (2002), o Lingua Franca core. Por fim, questões metodológicas são discutidas, ressaltando os diferentes focos estabelecidos nos estudos sobre inteligibilidade, assim como a miríade de variáveis contempladas em estudos internacionais que ainda precisam ser incorporadas em investigações no território nacional. Algumas dessas variáveis estão relacionadas ao falante, ao ouvinte, ou são de natureza linguística (proficiência na língua estrangeira, familiaridade com o sotaque, frequência lexical). Por fim, são apresentadas conclusões sobre os estudos envolvendo inteligibilidade e possíveis implicações para a sala de aula e para a pesquisa de cunho aplicado. Palavras-chave: Inteligibilidade; Inglês brasileiro; Método de pesquisa. Avaliação da pronúncia.